One-year Survival of End-Stage Kidney Disease Patients Undergoing Hemodialysis in Indonesia - Andhika R; Afiatin; Supriyadi R; Bandiara R; Sukesi L; Sudarmadi AP; Wahyudi K; Sofiatin Y (International Journal of Nephrology and Renovascular Disease)
Rizky Andhika,1 Afiatin,1 Rudi Supriyadi,1 Ria Bandiara,1 Lilik Sukesi,1 Adhika Putra Sudarmadi,1 Kurnia Wahyudi,2 Yulia Sofiatin3 1Division of Nephrology and Hypertension, Department of Internal Medicine, Hasan Sadikin General Hospital, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, Indonesia; 2Department of Public Health, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, Indonesia; 3Department of Epidemiology, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, IndonesiaCorrespondence: Rizky Andhika, Division of Nephrology and Hypertension, Department of Internal Medicine, Faculty of Medicine Padjadjaran University–Hasan Sadikin General Hospital, Jl. Pasteur no. 38, Bandung, 40161, Indonesia, Email rizkyandhikaipd@gmail.comBackground: Chronic Kidney Disease (CKD) represents a significant global health challenge, with Indonesia experiencing the highest surge in End-Stage Kidney Disease (ESKD) prevalence over the past decade. Kidney registries are essential for reporting health outcomes, evaluating healthcare services, advocating for policy change, and informing health infrastructure development. Survival rates in ESKD patients undergoing hemodialysis (HD) are a critical outcome measure. However, there is a lack of survival analysis data for ESKD patients receiving HD in Indonesia.Objective: This study aims to assess the one-year survival rate of ESKD patients undergoing HD in Indonesia, while examining risk factors associated with survival, including age, gender, CKD etiology, and dialysis adequacy.Methods: This analytical observational study employed a retrospective cohort design, utilizing patient data from Indonesia Renal Registry between 2016 and 2019. Kaplan-Meier survival curves were generated, and Log rank test was applied to assess the significance of survival differences across subgroups based on age, gender, CKD etiology, and dialysis adequacy.Results: A total of 122,449 ESKD patients on HD were analyzed, with a mean age of 52 years; majority (55.5%) were male, and hypertensive kidney disease was the leading cause of CKD (43.7%). The overall one-year survival rate was 91.5% (95% CI: 91.3– 91.6). Survival decreased significantly with advancing age (p < 0.01), and female patients exhibited lower survival rates compared to males (p < 0.01). Patients with diabetic nephropathy had the lowest survival rate among CKD etiologies (p < 0.01). Dialysis adequacy, assessed in 11,633 patients, revealed that 69.2% had a Kt/V below 1.8. Those with inadequate dialysis had significantly lower survival rates (p=0.00015).Conclusion: The one-year survival rate for ESKD patients undergoing HD in Indonesia is 91.5%. Increased age, female, diabetic nephropathy as the underlying CKD etiology, and inadequate dialysis adequacy are associated with reduced survival rates.Keywords: chronic kidney disease, hemodialysis, one-year survival, Indonesian renal registry